Advanced taekwondo - Shaw, Scott 1958-
In Advanced taekwondo, Scott Shaw presents an in-depth look at the complete art of Taekwondo-from the underlying philosophies that drive the techniques and strategies to advice on mastering basic and advanced techniques fundamental to the art. Chapters include: An in depth look at the origins and philosophies of Taekwondo; Discussion and tips on mastering essential techniques; Illustrated poomse sequences, including the Taeguek forms and Black belt forms; Effective strategies and skills for self-defense; Ewapons techniques including instruction in Kumdo, the Korean Art of the sword. With over 400 illustrations and detailed instruction from a leading teacher in the field, even the most experienced black belts can benefit from the lessons in this book